İşletmelerde iç kontrol yapısının yeri ve önemi - Güven, Fatih Mehmet (My University, 2008)
İç kontrol yapısı şirketlerin bütün departmanlarında gerçekleşen faaliyetlerin izlenebilmesi açısından kurulması zorunlu bir sistemdir. Dünyada yapılan düzenlemeler sonucunda, Türkiye’de de 2002 yılında çıkarılan Sermaye Piyasası Kurulu tebliği ile Sarbanes-Oxley doğrultusunda birtakım yasal düzenlemeler yapılmıştır. Örneğin, dış denetçilerin borsaya kayıtlı şirketlerin iç kontrol yapılarının oluşturulmasında sorumluluk almaları yasaklanmıştır. Yine bu tebliğ ile hisse senetleri borsada işlem gören ortaklıklar, denetimden sorumlu komite kurmalı ve bu komitede yönetim kurulunda murahhaslık sıfatı taşımayan en az iki üye bulundurmalıdırlar. Yeni Bankalar Kanununa göre, bankalar etkin bir iç kontrol yapısı kurmak ve işletmekle yükümlüdürler. Bağımsız denetim kuruluşları, çalışmalarında yöneticilerin esas sözleşmeye aykırı hususlarda bulunduğunu saptarsa bunun Bankacılık Düzenleme ve Denetleme Kurulu’na bildirilmesi istenmiş, sözkonusu faaliyetlerden ötürü üçüncü kişilere zarardan sorumlu tutulmuşlardır. Yeni Ticaret Kanunu tasarısında, iç kontrol yapısının tasarının ruhunda bahsedilmesine karşın içerik olarak yeterince belirtilmediği için, iç kontrol yapılarının varlığı ve etkinliği konusunda yönündeki bir düzenlemenin, tasarı metninde açıklanmasında fayda sağlayacaktır.

THE IMPORTANCE AND LOCATION OF INTERNAL CONTROL STRUCTURE IN ENTERPRISES Internal control structure is an imperative system to follow the activities that is happening in all departments of the enterprises. After the arrangements that have been done in the world, some legitimate arrangements were made in the direction of Sarbanes-Oxley with the declaration of Capital Markets Board which was also carried into the effect in Turkey in the year 2002. For example; the external supervisor’s rights of taking responsibilities are prohibited in establishing internal control structures of the enterprises that are enrolled to the stock market. Again with this declaration, co-partnerships that have their stocks traded on the stock exchange must construct a committee that is responsible of controlling and this committee should have at least two members who are not the executive directors in the administrative council. According to the New Banking Law, banks are bound by the law of establishing effective internal control structure and operating it. If the independent controlling institutes confirm that the administrators are breaking the rules of the main agreement in their works, then they should inform Banking Regulation and Supervision Agency and are considered as responsible of deficit through the third persons’ because of the said activities. In the new Trade Law Project, as the internal control structure is not specified well enough about its content although it is stated in the project’s spirit, it will be beneficial to explain a new arrangement in the project text taking care of the entity and the effectiveness of the internal control structures.
Keywords: İç Kontrol; İşetmeler_İç Kontrol